Establishing serum protein electrophoresis reference intervals in free-ranging barren-ground caribou (Rangifer tarandus granti) - Daleo, Maris J.; Lieske, Camilla; Cray, Carolyn; Beckmen, Kimberlee B. (Frontiers in Veterinary Science, 2026)
Barren-ground caribou (Rangifer tarandus granti) populations range in parts of Alaska, USA, and the Yukon Territory, Canada, and are culturally and nutritionally important to northern Indigenous communities and subsistence hunters. Baseline clinical metrics in free-ranging caribou can inform individual and population health, signal environmental change, and guide conservation efforts. Serum proteins, when quantified and examined using protein electrophoresis, can reflect nutritional status, metabolic issues, and organ function. However, reference intervals for these parameters are lacking in free-ranging caribou. This study established reference intervals for serum protein electrophoresis fractions in sera collected from free-ranging barren-ground caribou for the fall, spring, and summer seasons. From 1998 to 2024, 143 wild, apparently healthy breeding adults were captured across six herds in Alaska and Canada. Reference intervals were calculated for adult females in the fall (n = 35), summer (n = 34), and spring (n = 74), and for male and female yearlings (10–14 months; n = 53), following established guidelines by the American Association of Veterinary Clinical Pathology. The greatest seasonal divergence occurred between spring and fall in adult females, likely reflecting changes in pregnancy and nutrition. Protein concentrations also appeared to be useful for ruling out parasitic and bacterial infections than for detecting them; nonetheless, serum proteins provide a broad, early indication of nonspecific health disturbances. These season-specific reference intervals offer a baseline for assessing the health of free-ranging caribou herds.